New Mineral Species and Their Crystal Structures - Pekov, Igor V. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
One last comment concerns the fundamental contributions of Fourier analysis to quantum physics: Quantum mechanics and quantum field theory.